One-Pot Catalyst-Free Domino Condensation/Intramolecular 1,3-Dipolar Cycloaddition: Highly Stereoselective Access to Phosphadihydrocoumarin-Fused N,N-Bicyclic Pyrazolidin-3-ones - Wu, Mingshu; Jiang, Jie; Zhu, Zhongxiang; Wang, Qinghe; Kong, Dulin (Synthesis, 2018)
A concise, atom-economic, and highly regio/stereoselective synthetic strategy was developed for the construction of phosphorus- and nitrogen-fused polycyclic skeleton derivatives. The one-pot, two-step, catalyst-free domino condensation/intramolecular cycloaddition reaction of various substituted 2-(vinylphosphoryloxy)benzaldehydes with pyrazolidin-3-one took place at room temperature. Three new bonds (C–C, 2 × C–N) and two new nitrogen and phosphorus heterocycles were simultaneously constructed. The reaction is particularly attractive due to features such as low cost, mild conditions, atom economy, high stereoselectivity, and potential biological activity of the product.
Keywords: catalyst-free; stereoselectivity; nitrogen and phosphorus heterocycles; polycycles; intramolecular cycloaddition